Étude de l'impact de l'extension et de la densification du tissu urbain sur les coefficients de ruissellement dans le bassin versant des oueds El-Ghrich et El-Greb (Tunis) par l'application de la méthode SCS aux évènements de septembre 2003 - Noômène Fehri; Yadh Zahar (Physio-Géo)
September 2003 was exceptionally rainy in all Grand Tunis. During that month, the rainfall exceeded 345 mm. This represents 11 times its average observed in the station of Tunis-Carthage. These precipitations fell in a context characterized by the densification of the urban fabric and the waterproofing of grounds. The floods which resulted from it, made once again appear the debate on the respective weights of the climatic change and the human responsibility in the increase of the losses in human lives and the damage to property caused by these extreme phenomena.In Wadi El-Ghrich and Wadi El-Greb catchment, taken as example for this study, built surfaces rose from 5.7 % of the total surface in 1950 to 60.2 % in 1983 and then to 70.5 % in 2007. In the absence of a general scientific consensus on the impact which the global warming could have on the trends of the precipitations, one thing is sure : the extension and the densification of the buildings caused an indisputable increase of the coefficients of streaming of ponds hillsides and thus pulled a worsening of the flood risk. It is what we suggest demonstrating through a statistical approach as well as by the application of the model SCS.